Uma proposta de envoltória de resistência ao cisalhamento para solos arenosos artificialmente cimentados na região metropolitana de Fortaleza - Bastos, Ícaro José Fernandes Santos (2017)
Soils are particulate materials, which are often characterized by low shear strength. This aspect generally justifies adaptations in the geotechnical design to this characteristic, which may be even more problematic with soft sands, usually what occurs in surface layers throughout the Fortaleza Metropolitan Area (RMF). Therefore, the soil improvement procedure with addition of small fractions of cement can be extremely important. The adopted cement content should be such as to bring, for instance, a more economically and viable alternative to the geotechnical design of a surface foundation. In this case, the foundation geometric design, for example a shallow, will mainly depend on its load capacity, which will also depend on terrain's resistance properties. In the load capacity calculations, it is used geotechnical models pioneered proposed by Terzaghi that consider the most suitable soil rupture criterion is the one from Mohr-Coulomb. However, regarding soils artificially improved with cement that presents a substantial strength gain for each cement content, new Mohr-Coulomb strength parameters like cohesion and friction angle were obtained. This research proposes a modified Mohr-Coulomb envelope for artificially cemented soils. The proposal is based on the creation of two different functions to relate cohesion and friction angle with the cement content, very similar to what Fredlund et (1978) proposed for unsaturated soils improved by suction. In order to assess the proposed functions, triaxial shear tests were performed in sand with several cement contents. Adjustments were very similar. In addition, the envelope was applied for other tests published in the literature, proving the validity of this research proposal. Ultimately, the resistance envelope for cemented soils was applied in two hypothetical situations, a surface foundation and a slope. In both cases the main focus was on identify the most viable cement content in terms of safety and economy.